2018
DOI: 10.1007/978-3-319-96145-3_14
|View full text |Cite
|
Sign up to set email alerts
|

What’s Hard About Boolean Functional Synthesis?

Abstract: Given a relational specification between Boolean inputs and outputs, the goal of Boolean functional synthesis is to synthesize each output as a function of the inputs such that the specification is met. In this paper, we first show that unless some hard conjectures in complexity theory are falsified, Boolean functional synthesis must generate large Skolem functions in the worst-case. Given this inherent hardness, what does one do to solve the problem? We present a two-phase algorithm, where the first phase is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
88
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(88 citation statements)
references
References 39 publications
0
88
0
Order By: Relevance
“…It was recently shown [1] that unless some long-standing complexity theoretic conjectures are falsified, Boolean functional synthesis must necessarily require super-polynomial (or even exponential) space and time. In the same work [1], it was also shown that if a specification is represented in weak decomposable negation normal form wDNNF, synthesis can be accomplished in time polynomial in the size of the specification.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was recently shown [1] that unless some long-standing complexity theoretic conjectures are falsified, Boolean functional synthesis must necessarily require super-polynomial (or even exponential) space and time. In the same work [1], it was also shown that if a specification is represented in weak decomposable negation normal form wDNNF, synthesis can be accomplished in time polynomial in the size of the specification.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently shown [1] that unless some long-standing complexity theoretic conjectures are falsified, Boolean functional synthesis must necessarily require super-polynomial (or even exponential) space and time. In the same work [1], it was also shown that if a specification is represented in weak decomposable negation normal form wDNNF, synthesis can be accomplished in time polynomial in the size of the specification. While this was a first step towards identifying a normal form with the explicit objective of polynomial-time synthesis, experimental results in [1] indicate that wDNNF doesn't really characterize specifications that admit efficient synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations